Sex offender registries: exploring the attitudes and knowledge of political decision-makers. Issue 3 (3rd May 2020) - Jung, Sandy; Allison, Meredith; Toop, Carissa; Martin, Erin
Abstract : Sex offender registries (SORs) were established due to policies and practices intended to protect the public from individuals who commit sexually violent acts, and yet the empirical literature does not show that public SORs reduce or prevent sexual crimes. Given that politicians prominently influence SOR policies, the current study explores the views of SORs by 26 political decision-makers from Canada and the United States. Participants completed a survey on their opinions regarding SORs and their knowledge of SOR eligibility. Attitudes and political perspectives were assessed to examine their association with SOR opinions. Almost two thirds of those surveyed believed SORs should be publicly available, and one third believed SORs helped to protect the public. These beliefs were associated with those with conservative-leaning political views. These findings help us to explore the perspectives of political decision-makers and gain insight into attitudinal factors that may play a role in influencing opinions regarding SORs.